Application of Jean Watson's Theory of Human Caring Towards the Independence of HIV/AIDS Patients in Hospitals: A Systematic Review - Edi Susanto; Rusnoto Rusnoto; Fery Agusman Motuho Mendrofa (GLOBAL HEALTH SCIENCE GROUP, 2026)
HIV/AIDS is a global health problem that remains a major challenge, particularly regarding quality of life, stigma, and patient independence in long-term care. Jean Watson's Human Caring Theory offers a holistic approach that focuses on therapeutic relationships, respect for human dignity, and emotional and social support, potentially increasing the independence of HIV/AIDS patients in the hospital. This study aims to identify, synthesize, and analyze scientific evidence regarding the application of Jean Watson's Theory of Human Caring to increasing the independence of HIV/AIDS patients in hospitals. This study used a Systematic Review method with PRISMA guidelines. Literature sources were searched through Google Scholar, Semantic Scholar, ProQuest, and ScienceDirect for the years 2015–2025. The keywords used were human caring, Jean Watson, independence, PLWHA, HIV/AIDS, hospital. Of the 1,099 articles found, 8 articles met the inclusion criteria for further analysis. The review showed that the implementation of Human Caring improved communication, motivation, social interaction, medication adherence, and quality of life in HIV/AIDS patients. Factors such as family support, employment status, clinical condition, and psychosocial support were shown to influence patients' levels of independence. The caring approach also reduced stigma, strengthened self-confidence, and encouraged active patient involvement in care. Jean Watson's Theory of Human Caring has been shown to contribute significantly to increasing the independence of HIV/AIDS patients in hospitals through a holistic and multidimensional approach. Future research is recommended to develop a caring-based intervention model with more measurable effectiveness tests using experimental or quasi-experimental designs and incorporating independence as the primary indicator.